EMPOWERING MUSLIMAH STUDENTS’ AWARENESS ABOUT THEIR COSTUME: DESIGNING ENGLISH MATERIAL FOR ISLAMIC HIGHER EDUCATION - Widya Syafitri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
Todays globalization has changed the lifestyle of Indonesian Muslim women, especially in college. Islamic values have been many abandoned by them. For example, we can see the ethics in dress and wear of hijab that has been far from Islamic sharia. As a speech says